Screening of Hardhenu Crossbred, Sahiwal and Hariana Bulls for Autosomal Recessive Genetic Disorder Bovine Leukocyte Adhesion Deficiency (BLAD) - Magotra, Ankit; Yadav, A. S.; Malik, B. S.; Garg, Asha Rani (International Journal of Bio-resource and Stress Management, 2019)
The present study involved screening of Hardhenu crossbred, Sahiwal and Hariana bulls for autosomal recessive genetic disorder i.e Bovine Leukocyte Adhesion Deficiency (BLAD) using PCR based techniques. BLAD is a lethal autosomal recessive disease caused due to a point mutation (A→G) at nucleotide 383 in the CD18 gene which results in substitution of aspartic acid with glycine in the adhesion glycoprotein CD18. All animals under study were maintained at Cattle Breeding Farm, LalaLajpat Rai University of Veterinary and Animal Science (LUVAS), Hisar, India. About 5 ml blood was collected aseptically from jugular vein puncture into EDTA containing tubes, transported to the animal genomics laboratory and stored at -20 °C until genomic DNA extraction, which was carried out using Phenol Chloroform method. The targeted genomic area of interest was amplified by using simple PCR technique. The amplified PCR products were digested with TaqI restriction enzyme. The targeted amplicon of 357 bp after digestion of the PCR product, the normal allele in unaffected bull produced two fragments of 201 bp and 156 bp. All the animals under study were found to be free from Bovine Leukocyte Adhesion Deficiency. The molecular screening revealed that none of the bulls screened under study was carrier for BLAD. The present study suggests that the PCR and PCR-RFLP based technique could be employed as an efficient technique for screening of various genetic disorders for identification of carriers or affected animals before using them in breeding programs to minimize the spread of defective allele.